Ruqyah Therapy Based on Local Wisdom to Overcome Dissociative Trans Disorders in Patients at Home Ruqyah and Al-Qur'an Therapy - Riswanto, Deni; Younis, Tarek (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Healthy humans are not only healthy physically but also psychologically. Healthy humans are those who are free from physical and psychological disorders. Dissociative trance disorder is a psychological disorder, which cannot be taken lightly and needs to be addressed further. One way to overcome it is with ruqyah therapy based on local wisdom. This research was conducted on patients at the Ruqyah and Al-Qur'an Therapy House. This study aims to determine transdissociative disorders in patients at the Ruqyah House and Al-Qur'an Therapy and ruqyah therapy based on local wisdom in treating transdissociative disorders in patients at the Ruqyah House and Al-Qur'an Therapy. This research uses a qualitative method with a type of field research using a qualitative approach. After going through the results of research, transdissociative disorders in patients at the Ruqyah House and Al-Qur'an Therapy were caused by mental pressure factors that made them stressed, jinn disorders which were motivated by wrong defense mechanisms, and criminal acts of jinn. Symptoms include conscious and unconscious, such as frequent headaches, confusion, tremors, frequent strange dreams. The types include jinn inhabiting the patient's body and genie occupying parts of the patient's body. Ruqyah therapy based on local wisdom at the Ruqyah House and Al-Qur'an Therapy make dissociative trance disorder patients calmer. In practice, Rumah Ruqyah and Al-Qur'an Therapy integrates Islamic psychotherapy and variations of local wisdom by using bidara leaves and black cumin which are placed in a glass of water and ruqyah therapy prayers are read.